Measuring the Impact of Real Estate Credit Expansion on the Chinese Economy (2008 - 2018) - Jiahao, Pan (2022)
The main research objective of this thesis was to empirically explore the degree of debt default risk faced by Chinese real estate enterprises in the context of the bankruptcy of Evergrande Group and the subsequent measures taken by the Chinese government to protect the domestic market. The theoretical part of this paper aims to clarify the process of capital structure adjustment. The optimal capital structure theory is obtained by describing and comparing different capital theories. The purpose has been to summarize the existing views in the economic literature what is the impact of debt growth on the enterprise performance and summarize the arguments why it could not be optimal for the company to increase its debt continuously. The ultimate generalization of all the theories described could be that the change of company value with debt can be roughly divided into two stages. In the first stage, the bankruptcy cost is small when the company's debt level is low. In this stage, the company value rises rapidly with the increase in debt. In the second stage, when the debt level rises to a certain level, the company's value is maximized. According to the marginal effect analysis, the marginal tax avoidance income and marginal bankruptcy cost of the debt are equal. In the second stage, after critical level of debt is accumulated, the value of the company will gradually decrease with the further increase of the debt level. Next as a motivation for the research on the realization of the theoretic concepts in the Chinese real-estate market, an overview of the historical development of the latter is made. It provide historical background what caused the current high debt of China's real estate enterprises, and comments on the role of the Chinese government issued the "three red lines" policy the expansion of the debt default risk of Evergrande Group in year 2021.